The Effect Of Training, Career Path, And Compensation On Employee Performance At Pt Gosyen Pacific Suskesmakmur - Michael Michael; Pujiarti Pujiarti; Andy Andy (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
The purpose of this study is to test and find out how much influence training, career path, and compensation have on employee performance at PT Gosen Pacific Suksesmakmur. The sample determination in this research is an employee of PT Gosyen Pacific Suksesmakmur itself who is still actively working by using the Sampling technique saturated with a total of 50 respondents, the method in data collection is carried out using questionnaires and data processing using SPSS 25. The analysis used uses statistical models which include Frequency Test, Descriptive Test, Validity Test, Reability Test, Determination Test (R2), T Test, and F Test. The results obtained partially stated that the training variable (X1) had a significant effect with a calculated tcount> ttabel , the variable X2 career path had a significant effect with a calculated tcount> ttabel , the variable X3 compensation had no significant effect with a calculated tcount< ttabel . The results obtained simultaneously fcount> ftabel 104,824 > 2.57 training, career path, and compensation have a significant effect on employee performance, so it can be concluded that independent variables affect dependent variables.